Kirk-Othmer Encyclopedia of Chemical Technology 2007
DOI: 10.1002/0471238961.1915141519211912.a01.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemistry

Abstract: Sonochemistry is a relatively new term that arrived on the scene in the late 1970s and was then simply defined as the uses of ultrasound in chemistry and processing. Ultrasound is part of the overall sound spectrum, but is generally classified as sound beyond the frequency that can be detected by the human ear. Sometimes called “silent sound” it ranges from 20 kHz to 10 MHz within which it can be roughly subdivided into three main regions: low frequency, high power ultrasound (20–100 kHz); intermediate frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 128 publications
2
59
0
Order By: Relevance
“…13 The effect of Tween 40 concentration on particle size D [3,2] of flaxseed oil in water emulsion prepared by microfluidisation (Reproduced with permission from [38]) by forcing it through a 10 mm orifice atomizer. The winemist was collected after 4, 8, 12 and 16 passes and compared to conventionally aged rice and maize wines, respectively.…”
Section: Ageing Of Winementioning
confidence: 99%
See 1 more Smart Citation
“…13 The effect of Tween 40 concentration on particle size D [3,2] of flaxseed oil in water emulsion prepared by microfluidisation (Reproduced with permission from [38]) by forcing it through a 10 mm orifice atomizer. The winemist was collected after 4, 8, 12 and 16 passes and compared to conventionally aged rice and maize wines, respectively.…”
Section: Ageing Of Winementioning
confidence: 99%
“…It is for this reason that sonication of air-saturated solutions can lead to a decrease in the pH. Further details of the phenomenon of acoustic cavitation have been described elsewhere [2] and the reader is directed to this review article.…”
Section: Introductionmentioning
confidence: 99%
“…Bioeffects caused by acoustic streaming have been confirmed to occur in cell cytoplasm [19]. The second type comprises cavitation effects, which consist of both chemical and physical effects, for example, free radical reactions, shock waves, shear stress, and microjet [20]. Although chemical effects have been reported as a major cause of inactivation [21], inactivation mechanisms due to shock waves [22] and shear stress of microstreaming [23] have also been suggested.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasounds can promote for realizing many reactions [11][12][13], most of the effects arise from cavitations [14][15]. In the literature, it is shown that increase in yield is observed upon condensation reaction using ultrasounds.…”
Section: Resultsmentioning
confidence: 99%